2021
DOI: 10.1111/resp.14003
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 expression is elevated in airway epithelial cells from older and male healthy individuals but reduced in asthma

Abstract: ACE2 is the primary receptor for SARS‐CoV‐2. We demonstrate that lower airway expression of ACE2 is increased in older adults and males. Lower ACE2 expression in epithelial cells also occurs in people with asthma and is associated with reduced furin and increased ADAM‐17 expression. This may partly explain the relative sparing of people with asthma from severe COVID‐19.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 49 publications
1
65
0
1
Order By: Relevance
“…For example, in nasal epithelium, a critical site of SARS-CoV-2 entry, ACE2 gene expression increases with age [ 143 ]. Similarly, a recent study found ACE2 gene expression in airway epithelial cells higher in older male patients, even as its expression pattern varied in other organs and in women [ 144 , 145 ]. Lastly, sACE2 levels are elevated in numerous high-risk groups [ 43 , 44 , 146 ].…”
Section: Evidence For Ace2 Downregulation Modelmentioning
confidence: 93%
“…For example, in nasal epithelium, a critical site of SARS-CoV-2 entry, ACE2 gene expression increases with age [ 143 ]. Similarly, a recent study found ACE2 gene expression in airway epithelial cells higher in older male patients, even as its expression pattern varied in other organs and in women [ 144 , 145 ]. Lastly, sACE2 levels are elevated in numerous high-risk groups [ 43 , 44 , 146 ].…”
Section: Evidence For Ace2 Downregulation Modelmentioning
confidence: 93%
“…A previous study has also found decreased ACE2 expression in a rat model of COPD exposed to cigarette smoke [75] . In another study, ACE2 expression in the airway epithelium was lower in asthmatic patients but not significantly different between COPD patients and healthy controls [76] . Therefore, the evidence is still conflicting regarding the impact of COPD and smoking on the cellular ACE2 expression.…”
Section: Introductionmentioning
confidence: 90%
“…RNA sequencing of upper and lower airway cells from three different cohorts including children and adults identified asthma and respiratory allergies to be associated with significantly reduced ACE2 expression ( 43 ). Age and male sex are known risk factors for COVID-19 and accordingly, increased expression of ACE2 was noted in the airways of older population and males ( 44 ). In patients with asthma, the reduced gene and protein expression of ACE2 was accompanied by lower expression of furin, a protease that cleaves the spike glycoprotein, and higher expression of ADAM-17 , a disintegrin that cleaves ACE2 from the surface ( 44 ).…”
Section: Implications Of Asthma Pathobiology On Covid-19 Pathogenesismentioning
confidence: 99%
“…Age and male sex are known risk factors for COVID-19 and accordingly, increased expression of ACE2 was noted in the airways of older population and males ( 44 ). In patients with asthma, the reduced gene and protein expression of ACE2 was accompanied by lower expression of furin, a protease that cleaves the spike glycoprotein, and higher expression of ADAM-17 , a disintegrin that cleaves ACE2 from the surface ( 44 ). COVID-19 patients with asthma were also characterized by a reduction in ACE2 protein expression in their lower airways, when compared with COVID-19 subjects without asthma ( 45 ).…”
Section: Implications Of Asthma Pathobiology On Covid-19 Pathogenesismentioning
confidence: 99%